MICROTOPOGRAPHIC EVOLUTION OF MINERAL SURFACES AS A TOOL TO IDENTIFY AND DATE YOUNG FAULT SCARPS IN BEDROCK - Mayer L.; Rakovan J.; Rufe E. (My University, 2000)
Faulting that results in surface ruptures through bedrock can be particularly difficult to date. For example, stratigraphic control on the age of faulting, based on the age of the bedrock, often leaves unacceptably large uncertainty on the age of the faulting. From a paleoseismological perspective, there is a clear need to determine if a bedrock fault scarp is actually a young feature. For young fault ruptures that create fresh mineral surfaces, analysis of microtopography developed by weathering of the mineral surface may provide a quantifiable method for determining the fault age. The direct quantitative measurement of mineral surface microtopography using Atomic Force Microscopy affords a novel method to study the rupture ages of active faults. The method for using microtopographic evolution of mineral surfaces depends on three conditions. The first condition is that freshly exposed mineral cleavage surfaces, which can be described geometrically as planes, are formed during a rupture event. The formation of these fresh surfaces is analogous to the initiation of a weathering 'clock' that defines time t=0. Following cleavage formation dissolution of the planar mineral surface occurs. The rate of dissolution for a mineral species under given climatic conditions, governs the rate of mineral surface alteration. Thus as dissolution proceeds, the roughness of the mineral surface increases. We suggest that the progression of microtopographic roughness over time, which can be estimated by computing quantitative statistics derived from digital mineral surface topography, will systematically vary until a steady state surface topography is reached. The fractal dimension, Df, is one such measure of surface roughness where, Df at time t=0 is 2. The dissolution of the mineral surface increases the fractal dimension as the removal of material proceeds. We posit that somewhere between Df=2 and Df=3, the microtopography reaches a steady state. Therefore, in the pre-steady state stage of surface roughness, the quantitative measure of roughness of the mineral may serve as a measure of time elapsed since faulting. The period of time this initial stage of surface roughening represents is dependent on the mineral and as a consequence, its dissolution rate, in a specific set of environmental conditions. The time elapsed since fault rupture and grain cleavage can also be estimated from the measurement of the volume of material removed through dissolution. If part of the original cleavage surface remains and can be identified then AFM measurements of the surface microtopography can be used to calculate the dissolved volume per unit area.